Penerapan Metode SOSTAC dalam Perancangan Sistem Informasi Space Rent UMKM Stasiun - Rugaiyah Balqis; Pacu Putra; Nabila Rizky Oktadini; Alsella Meiriza; Putri Eka Sevtiyuni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The provision of Space rent or space rental for LRT station MSMEs in Palembang City is a form of sensitivity and concern for economic growth in Indonesia. Currently, the dissemination of information regarding the provision of space rent for MSMEs is only limited to several social media such as Facebook and Instagram. This research aims to be able to provide new opportunities in the form of designing a marketing information system for Space rent UMKM at the Palembang City LRT station using a website. System design must be by applying methods that can formulate, control, and evaluate the system so that it can be right on target according to user needs. This research is a descriptive qualitative research using the results of the analysis of direct interviews with five informants consisting of business development parties of the South Sumatra Light Railway Management Center, station UMKM business actors, and the general public which are used as reference materials for the formulation of analyses into the method used, namely the SOSTAC method which is implemented through a prototype website and tested through blackbox testing. The results of this research are in the form of the Palembang City LRT Station Space rent MSME website which can be used as a marketing media and MSME sales information system according to user needs. Based on testing through blackbox testing, it was found that the Palembang City LRT Station UMKM Space rent website had run well.